PENGARUH TAHAP-TAHAP KETERAMPILAN METODE UMMI TERHADAP KEMAMPUAN MENGHAFAL AL-QUR’AN SDIT BINA INSAN KRAGILAN - Fatkha, Magfirotul; Sujono , Ujon; Kulsum , Umi (Staisman Press, 2024)
The Ummi method is one of the methods of reading the Qur'an that directly includes and practices tartil reading according to the rules of tajwid science using a mother tongue approach that emphasizes affection with the classical reading and listening method and a quality assurance system. by carrying out the stages of the Ummi method skills, one of which is by repeating memorization, this can help in memorizing so that students can memorize well according to the rules of tajwid science. The objectives of this study are: 1. To determine the influence of the stages of the Ummi method skills in learning the Qur'an at SDIT Bina Insan Kragilan. 2. To find out how the ability to memorize the Qur'an is at SDIT Bina Insan Kragilan. 3. To find out how much influence the stages of the Ummi method skills have on the ability to memorize the Qur'an at SDIT Bina Insan Kragilan. This type of research is quantitative research using descriptive statistical analysis. The results of the study showed 1. The stages of the ummi method skills in learning the Qur'an at SDIT Bina Insan Kragilan were quite good, this was evidenced by the results of the questionnaire with a percentage of 66.58%. 2. The ability to memorize the Qur'an at SDIT Bina Insan Kragilan was good, this was evidenced by the results of the questionnaire with a percentage of 71.33%. 3. There was an influence of the stages of the ummi method skills on the ability to memorize the Qur'an, this was evidenced by the T test which showed a Tcount value of 4.578 Ttable 2.017. And the coefficient of determination value was 32.8% while the remaining 67.2% was obtained by other factors.